2014
DOI: 10.3349/ymj.2014.55.3.725
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood Interferon-γ Release Assay Is Insufficient for the Diagnosis of Sputum Smear Negative Pulmonary Tuberculosis

Abstract: PurposeWe investigated the value of an interferon-γ release assay (IGRA) for the diagnosis of active pulmonary tuberculosis (PTB) among sputum smear negative PTB suspects in an environment with intermediate burden of PTB and high Bacillus Calmette-Guérin (BCG) vaccination rate.Materials and MethodsWe retrospectively reviewed IGRA, medical records, chest PA and CT scan of PTB suspects seen at Gangnam Severance Hospital, Seoul, Korea from Oct. 2007 to Apr. 2013. "Active PTB" was diagnosed when 1) M. tuberculosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the small group of UMRs assessed here, no cases of active tuberculosis were identified by chest x-ray, which is a standard screening tool for active pulmonary tuberculosis for migrants coming to Germany. Although some authors describe that the sensitivity of gamma-interferon release assays is higher than that of chest x-ray for the diagnosis of active pulmonary tuberculosis in sputum-negative patients [ 24 ], a recent literature review indicated that chest x-rays have acceptable to good sensitivity for the diagnosis of pulmonary tuberculosis [ 25 ]. Further, the positive predictive value of gamma-interferon release assays for the diagnosis of active tuberculosis is low for patients from high-endemicity settings because positive results can also be expected in cases of latent or cured tuberculosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the small group of UMRs assessed here, no cases of active tuberculosis were identified by chest x-ray, which is a standard screening tool for active pulmonary tuberculosis for migrants coming to Germany. Although some authors describe that the sensitivity of gamma-interferon release assays is higher than that of chest x-ray for the diagnosis of active pulmonary tuberculosis in sputum-negative patients [ 24 ], a recent literature review indicated that chest x-rays have acceptable to good sensitivity for the diagnosis of pulmonary tuberculosis [ 25 ]. Further, the positive predictive value of gamma-interferon release assays for the diagnosis of active tuberculosis is low for patients from high-endemicity settings because positive results can also be expected in cases of latent or cured tuberculosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that the T-SPOT.TB assay is a promising diagnostic test for active PTB,[ 6 7 8 ] but other studies showed that IGRA was insufficient for the diagnosis of PTB. [ 9 10 ] In this study, we conducted a large retrospective multicenter investigation in China to further evaluate the use of IGRA in the diagnosis of active PTB in high TB-epidemic populations and the factors affecting the performance of the assay.…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen studies [ 2 10 , 23 27 ] reported the diagnostic accuracy of QFT-GIT, while 5 studies [ 10 , 25 , 26 , 28 , 29 ] reported the diagnostic accuracy of T-SPOT.TB. No study of QFT-GIT-plus was identified.…”
Section: Resultsmentioning
confidence: 99%